Politik Hukum Perubahan Undang-Undang Kejaksaan terkait Kerjasama dengan Lembaga Penegak Hukum dan Instansi Lainnya - Alfy Nazah Aulia; Arfiani Arfiani; Henny Andriani (Lareh Law Review, 2023)
Legal politics is necessary for examining the changes that need to be made to Law Number 16 of 2004 concerning the Prosecutor's Office to meet the needs of society. An analysis in Article 33 of the aforementioned law, which shows how crucial law enforcement agencies are in collaborating in the implementation of state power. The purpose of this article is to understand the legal politics of change and the implications of changes in collaboration regulations between the Prosecutor's Office and other law enforcement agencies and institutions. This article uses a Normative Juridical method. The research findings are as follows: first, the legal politics of the changes in Law Number 16 of 2004, which became Law Number 11 of 2021 on amendments to Law Number 16 of 2004 concerning the Prosecutor's Office, especially in Article 33 related to the collaboration of the Republic of Indonesia's Prosecutor's Office with other law enforcement agencies and institutions, were established to determine the position of the Prosecutor's Office in law enforcement in Indonesia. Therefore, the Prosecutor's Office collaborates with other law enforcement agencies and institutions to achieve the goals of the Prosecutor's Office itself. Second, the implications of the changes in Article 33 of the aforementioned law have an impact on the role of the Prosecutor's Office in the performance of prosecution, which can collaborate with various national and international law enforcement agencies, including institutions or organizations. Collaboration between the Prosecutor's Office and other law enforcement agencies can be seen in Memorandums of Understanding (MoUs).